2021
DOI: 10.33631/duzcesbed.833024
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Optimization, and In-Vitro Evaluation of Hyaluronic Acid Buccal Films Containing Benzydamine Hydrochloride

Abstract: Aim: Mucoadhesive buccal films provide drug delivery for both local and systemic circulation with increased patient compliance. The objective of this study was to develop a buccal film containing benzydamine hydrochloride (BNZ) by using hyaluronic acid (HA) as a film-forming agent and glycerin (Gly) as a plasticizer for the anti-inflammatory effect on the mucosal ulcer. Material and Methods: The effects of different concentrations of HA and Gly on responses were analyzed using 2 3 factorial design. The HA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Particularly, in this model, it has been found that the aqueous extract of Iceland lichen causes an augmented secretion of IL-10 and IL-12p40 as anti-inflammatory cytokines [ 36 ]. Moreover, this compound is also most commonly used to alleviate colds, coughs, mouth irritation, and respiratory issues because, among other things, it is associated with the absence of side effects or interactions, and has also been studied for the treatment [ 37 ]. As assessed regarding the interference with the cell oxidation status, the marked decrease of cytokine release induced by the complete combination, including in the case of LPS proinflammatory stimulus, following a still unknown mechanism makes RIPACUT ® highly deserving of scientific interest for future experiments of molecular characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, in this model, it has been found that the aqueous extract of Iceland lichen causes an augmented secretion of IL-10 and IL-12p40 as anti-inflammatory cytokines [ 36 ]. Moreover, this compound is also most commonly used to alleviate colds, coughs, mouth irritation, and respiratory issues because, among other things, it is associated with the absence of side effects or interactions, and has also been studied for the treatment [ 37 ]. As assessed regarding the interference with the cell oxidation status, the marked decrease of cytokine release induced by the complete combination, including in the case of LPS proinflammatory stimulus, following a still unknown mechanism makes RIPACUT ® highly deserving of scientific interest for future experiments of molecular characterization.…”
Section: Discussionmentioning
confidence: 99%